High resolution single strand conformation polymorphism analysis using formamide and ethidium bromide staining. Issue 5 (October 1997) - Xie, T; Ho, S L; Ma, O C
Abstract : Single strand conformation polymorphism (SSCP) analysis using ethidium bromide can be improved by adding formamide as the denaturant. This gives higher resolution than previous SSCP methods; it had 100% sensitivity in the discrimination of 14 PCR samples from two different genes, even for a long fragment close to the upper limit of 250 base pairs. This modified procedure is a rapid, simple, safe, and yet highly sensitive method for detecting structural differences in DNA fragments.